94 Flow-Contraction Matching in The Human Heart: A Novel Invasive Study of The Complex Cardiac-Coronary Interaction in Ischaemic Heart Disease. (3rd June 2016) - Patterson, Tiffany; Rivolo, Simone; Arri, Satpal; Clapp, Brian; Perera, Divaka; Marber, Michael; Lee, Jack; Redwood, Simon
Abstract : Background: A first-in-human study of simultaneous invasive real-time left ventricular (LV) and coronary haemodynamics in the cardiac catheter lab enabling accurate delineation of the complex cardiac-coronary interaction and influence of antianginal therapy in coronary artery disease (CAD). Method: 15 patients completed the protocol (Figure;A&B ). Coronary measurements (baseline and 1 mg isosorbide dinitrate, ISDN) were performed with dual sensor pressure-flow wire (ComboWire®) advanced down coronary artery (C) and were electronically routed into the intracardiac analyser (CD Leycom, Netherlands) via which LV haemodynamics – using pressure-volume (PV) loop catheter in LV apex – were measured, thus enabling simultaneous recordings. Coronary blood flow (CBF), wave intensity analysis and LV pressure volume loops were analysed with specially developed in-house software (MatLab R2014b) (E); (paired t-test; linear regression). Results: Accurate delineation and timings of the backward and forward waves were described relative to cardiac contraction and relaxation (F). Backward expansion wave (BEW) occurred during isovolumic relaxation and correlated for the first time with peak dpdt- (r 2 0.4 p = 0.0015) and found to be load dependent (F); forward compression wave (FCW) occurred immediately following peak dpdt+; ISDN drove leftward, downward shift of PV loop (D) accompanied by two-step cardiovascular response 1) significant afterload reduction (endsystolic pressure 127+/-±23;98±22 mmHg; p < 0.01) associated with reduction in cardiac work (pressure volume area 1.4±0.4;1.1±0.4J) total peripheral resistance and arterial elastance representing systemic vasodilation and significant improvement in mechanical efficiency (68 to 74%) 2) Reduction in preload (14±5;10±5 mmHg; p < 0.01) was associated with improved passive (EDPVR B) and active (Tau) diastolic relaxation (38±4;36±4 ms; p < 0.01). Despite a reduction in perfusion pressure, coronary flow was maintained. Conclusion: For the first time in humans we relate coronary flow to cardiac contraction-relaxation and describe how ISDN exerts an anti-anginal effect by reduction in afterload and preload, therefore cardiac work and improved cardiac efficiency, maintaining coronary flow despite reduction in perfusion pressure, thus vastly increasing our understanding of the integrated cardiovascular response.